The Role of Islamic Religion Teachers in Improving Student Discipline during the Pandemic - Yayat Suharyat; Karsuhanah Karsuhanah; Nomin Nomin (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to identify the efforts of Islamic teachers and Budi Pekerti to instil disciplined attitudes in their students. This study focused on primary school and used qualitative research, case study methods, and research processes that generate descriptive data in the form of written or verbal data from people and observable behaviour as research subjects. It is concluded that the efforts of Islamic religious education and morality teachers to train students include maximizing the teacher's role both within the curriculum and in extracurricular activities. During the initial awareness of learning, disciplining students by keeping them focused on learning, disciplining students by providing guidance, and motivating teaching by inviting enthusiastic students to learn. In a co-curricular framework, this is done by assigning additional assignments and assessments after home visits for learning (post-testing). Supportive factors come from inside and outside the school. Barrier factors include minimal facilities, limited teachers, technical stuttering, low student motivation, the economic level of the community, and a limited school budget. Teachers and other stakeholders are expected to support various school programs to build discipline.